Implementation of the Sidogiri Qur'an Method in Improving the Fast Way of Reading the Qur'an at the Zainul Anwar Islamic Boarding School - Siti Mutmainah; Zakiyah BZ (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research explains the implementation of the Sidogiri Qur'an Method (MQS) in improving the fast way of reading the Al-Qur'an at the Zainul Anwar Islamic Boarding School. The Sidogiri Qur'anic method is an integrated approach to learning the Koran which has received widespread attention in the world of Islamic education. The Zainul Anwar Islamic boarding school in Alassumur Kulon utilizes the application of reading the Koran using the Sidogiri Qur'an method which was pioneered by a Salaf Islamic boarding school located in Pasuruan with the name